MR Angiographic Demonstration of Bilateral Duplication of the Extracranial Vertebral Artery: Unusual Course and Review of the Literature - Ionete, C.; Omojola, M.F. (American Journal of Neuroradiology, 2006)
SUMMARY:Duplication of the vertebral artery is a rare developmental anomaly. Duplication and fenestration are terms often used incorrectly and interchangeably in the literature. To the best of our knowledge, this is the first report to describe bilateral duplication of the extracranial vertebral artery. Bilaterally, there are 2 separate origins of each vertebral artery from the corresponding subclavian artery, with one duplicated segment entering the C7 foramen transversarium bilaterally and the other segment entering the carotid space on either side. The duplicated vessels join together at C5–C6 disk level on the left and at C4–C5 disk level on the right before continuing as one vessel in the foramina transversaria on either side. Duplication is thought to represent failure of controlled regression of 2 intersegmental arteries and a segment of the primitive dorsal aorta. This case was discovered on a 2D time-of-flight and contrast-enhanced neck MR angiogram in an 83-year-old man with cognitive decline and appears as an incidental finding without obvious clinical implications.